2009
DOI: 10.1045/march2009-ding
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Social Networks: A Social Tagging Perspective

Abstract: --Data mediation and interoperation have already become one of the central topics of IT for decades. Since the Web appears, this problem has been exploded due to the increasing amount of data and Web users. This paper takes look at the social tagging behavior. It proposes Upper Tag Ontology (UTO) to model tag data from three popular social tagging networks (del.icio.us, youTube, flickr). In this paper, we discuss how to crawel tag data and store them according to UTO in RDF triple store. Furthermore, based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Based on a review of the 1,300 most frequently assigned tags in the combined set of tags from Delicious, Flickr, and YouTube for the years 2005, 2006, and 2007, certain tagging behaviors were identified (see Table 8; for an alphabetical listing of all 1,300 tags, see Ding et al, 2009). For example, taggers often date objects by assigning tags for the current year or month; this is especially prevalent in Flickr, where the current year is always among the top-ranked tags (see Table 6).…”
Section: Tagging Patternsmentioning
confidence: 99%
“…Based on a review of the 1,300 most frequently assigned tags in the combined set of tags from Delicious, Flickr, and YouTube for the years 2005, 2006, and 2007, certain tagging behaviors were identified (see Table 8; for an alphabetical listing of all 1,300 tags, see Ding et al, 2009). For example, taggers often date objects by assigning tags for the current year or month; this is especially prevalent in Flickr, where the current year is always among the top-ranked tags (see Table 6).…”
Section: Tagging Patternsmentioning
confidence: 99%
“…Refactoring is a programming practice in which we look at a computer system, identify parts that are confusing, inefficient, or redundant, and then systematically improve them—all while making sure that the functions of the program do not change (Hendler, 2007 ; Ding et al, 2009 ). We propose a refactoring of the scholarly journal system.…”
Section: Introductionmentioning
confidence: 99%
“…Like a great number of online social networks, social tagging networks are considered as evolving and providing more and more information over time. (Ding et al, 2009) analysed tags frequencies across time and found that changing trends in user's interests can be identified and tracked over time. To extract the relevant information from this kind of data, we have to take into account this dynamic characteristic (see section 2.3).…”
Section: Tag-based User Profilingmentioning
confidence: 99%
“…For new or less-active users that interact less frequently with the system, their profile can be empty or does not contain any useful interests for a mechanism of customization or recommendation. Several works (Tchuente et al, 2013) (Carmel et al, 2009) (Ding et al, 2009) propose to use information from user's social networks.…”
Section: Introductionmentioning
confidence: 99%